Influence of facilities of ski preparation on the bodily condition of teenagers 11-12 years. - Vorona V.V (Kharkov National Pedagogical University, 2011)
The indexes of bodily condition of teenagers were determined. A dynamics and increase of the explored indexes were analyzed in the process of ski preparation in the system of lessons of the physical culture of schoolchildren. The 156 teenagers at the age 11-12 years old took part in the experiment. The positive effect of ski training in the bodily condition of the investigated teenagers is proved. Reliable intercommunication was determined between the ski movements and indexes of bodily condition, which characterize work of the cardiovascular system.